Health issue: Excessive smartphone usage among students in public university in Selangor, Malaysia from an ergonomic perspective - Radzlan, Rohaizahtulamni; Mohd Yusoff, Irwan Syah; Abd Halim, Muhammad Shaifudin (Human Resource Management Academic Research Society, 2023)
The number of smartphone users in Malaysia is expected to reach 29 million by 2021. The objective of this research is to examine the effects of excessive smartphone usage on the health of public university students in Selangor, Malaysia, from an ergonomic perspective. A cross-sectional study was involving a sample of 200 students enrolled in public universities located in the Klang Valley region. Purposive sampling was used, and data was collected through self-administered. The data was analysed using SPSS software and the Chi-square statistical test was employed. The majority of respondents were in the age range of 22 to 23. The findings indicated a noteworthy correlation between health issues related to musculoskeletal disorders (r = 0.000, p = 0.330). Research has demonstrated that the excessive utilisation of smartphones can exert detrimental effects on human well-being, encompassing both physical and emotional dimensions. The advent of smartphone has had a profound impact on cultural norms and human conduct, with discernible effects in both good and negative domains. The extent to which smartphone exert detrimental influence on society is largely contingent upon the agency and efforts of individuals to regulate and mitigate such effects.